Cultural Migrations in France and Italy: Travel Literature from Translation to Genre - Smecca, Paola (TTR)

(untitled) (Association canadienne de traductologie, 2003)
AbstractThis is a study on the role played by translations in the establishment of travel writing as a literary genre in Italy and partly in France. In fact, through translations, this heterogeneous production eventually defined its own characteristics and norms. In the eighteenth and nineteenth centuries most works were known to the Italian public through their French versions, often full of interpolations altering the original standpoints of the authors. As a consequence, the content of the texts and the cultural perceptions of travel writers ran the risk of being deeply modified and detached from the reality of the country visited.